ActivPAL™ determined sedentary behaviour, physical activity and academic achievement in college students. Issue 20 (18th October 2018) - Felez-Nobrega, Mireia; Hillman, Charles H.; Dowd, Kieran P.; Cirera, Eva; Puig-Ribera, Anna
ABSTRACT: The aim of this study was to examine relationships between activPAL™-determined sedentary behavior (SB) and physical activity (PA) with academic achievement. A total of 120 undergraduates (N = 57 female; 20.6 ± 2.3 years) participated in the study. Academic achievement was measured as the grade point average obtained from all completed courses. Participants wore on the right tight an activPAL™ for 7 days to determine total sedentary time, total number of sedentary breaks, sedentary bouts, standing time, light and moderate-to-vigorous physical activity (MVPA). Separate multiple linear regression models were performed to examine associations between SB variables and academic achievement. Light PA, MVPA, total sedentary time, total standing time, or total number of sedentary breaks were not related to academic achievement. Independently of PA, the amount of time spent in sedentary bouts of 10-20min during weekdays was positively related to academic achievement. Given that college students spend the majority of their workday in environments that encourage prolonged sitting, these data suggest that interruptions in prolonged periods of sitting time every 10-20min via short breaks may optimize cognitive operations associated with academic performance.